Gestión administrativa y su incidencia en la asignación de recursos financieros en el gobierno autónomo descentralizado, cantón buena fe año 2023 - Sánchez Yugcha , José Ricardo (2025)
Administrative and financial management in local governments is a key component for institutional development and the efficient use of public resources. In this context, the aim was to strengthen administrative processes and the allocation of financial resources in the Decentralized Autonomous Government of the Buena Fe canton through the formulation of strategies that address the identified internal needs. The research adopted a quantitative approach with a descriptive scope, using structured surveys applied to institutional personnel and complemented by document analysis. The results revealed weaknesses in internal organization, the absence of a defined institutional philosophy, lack of updated job manuals, deficiencies in budget control, and limited mechanisms for evaluating human talent performance. In response, three technical strategies were proposed: one for administrative management, focused on organizational redesign and internal processes; another for financial management, centered on the formalization of procedures and accountability; and a third aimed at strengthening human talent through continuous training and systematic evaluations. It is concluded that the progressive implementation of these strategies would contribute to the comprehensive improvement of institutional management, enabling a more efficient, transparent administration aligned with the principles of good governance.